An Overview of Islamic Law on the Tingkeban Tradition In Javanese society (Case Study in Laman Bukit Village, Belimbing District, Melawi Regency) - Nia Maulina (UNIVERSITAS PAKUAN, 2026)
This research aims to evaluate the Javanese tingkeban tradition from the perspective of Islamic law, with a focus on Laman Bukit Village, Belimbing District, Melawi Regency. This tradition involves giving gifts to pregnant women to celebrate the upcoming birth. The research employs qualitative methods and a case study approach to delve into the understanding and analysis of the tingkeban tradition and to assess its compatibility with Islamic teachings. The research findings indicate that the tingkeban tradition is a rich cultural heritage of the Javanese community that also reflects elements of religion. From the perspective of Islamic law, this tradition can be considered a positive practice as it expresses gratitude, togetherness, and sharing. However, the study also identifies aspects that need careful evaluation, such as its alignment with religious principles, differences in interpretation, and the potential for misuse. In this context, the research provides practical recommendations for the Javanese community to conduct the tingkeban tradition in accordance with Islamic values. These recommendations include enhancing the understanding of religious values related to the tingkeban tradition, integrating Islamic legal principles in its implementation, and emphasizing transparency and fairness in the management and execution of contributions. It is hoped that this research will offer valuable guidance to the Javanese community in preserving their cultural tradition while considering the strong principles of Islam in the process. Keywords: Islamic Law, Javanese Society, Tingkeban.